Qualidade da carne de cordeiros suplementados com vitamina E - Gilmara da Silva Melo, Gilmara (2015)
The sheep industry in Brazil is presented as a promising activity, not only for increased consumption of meat of this species, but also the future possibility that sees both the national and international market. Among many factors that can contribute to the consolidation of this activity, the quality of meat is the main factor. Although the demand for lamb is high, supply is low and unstable, being a limiting factor in the marketing of this product in addition to the lack of concise information of the quality characteristics and physical-chemical profile. Based on the above, the aim of this research was to determine the pH, color, tenderness, weight loss by cooking, water holding capacity and profile of fatty acids from lamb supplemented with vitamin E. The experiment was conducted in partnership with the Animal Science Department of Universidade Federal de São João del Rei (UFSJ) and analyzes were sent for analysis to the Department of Food science at the Universidade Federal def Lavras and Meat Technology Laboratory of the Universidade Estadual Paulista, campus Jaboticaba. Twelve Texel lambs were used with initial average weight of 25 kg and 42 kg final. And the diet consisted of hay Tifiton 85, ground corn, soybean meal and commercial mineral supplement formulated according to recommendations of NRC (2007), with or not vitamin E. The experimental design was completely randomized with two treatments and six replications. Data were analyzed by the GLM procedure of the SAS (2001) and the averages compared by test T at 5% probability. In this study, the use of vitamin E depreciated the quality of sheep meat.